Estimate of third Hankel determinant for a subfamily of analytic functions - Shah Syed Ghoos Ali; Hussain Saqib; Lateef Shahid; Sakar F. Müge; Darus Maslina (Annals of the West University of Timisoara: Mathematics and Computer Science, 2023)
In this article, our aim is to study analytic functions related with Salagean operator and associated with the right half of the lemniscate of Bernoulli. We find the estimates of the third Hankel determinant for new family of analytic functions. It is important to mention that our results generalize a number of existence results in the literature.